2011
DOI: 10.1002/jbm.b.31944
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a biodegradable novel periosteal distractor

Abstract: The new device is slim, biodegradable and the procedure is simple. Thus, periosteal distraction with this device is potential for vertical and horizontal ridge augmentation in oral cavity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 25 publications
1
32
1
Order By: Relevance
“…There was no control group to compare the results; however, in our previous studies, 11,40 we used devices to elevate the periosteum and overlying soft tissue without any secluding membrane in the same calvarial rabbit model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no control group to compare the results; however, in our previous studies, 11,40 we used devices to elevate the periosteum and overlying soft tissue without any secluding membrane in the same calvarial rabbit model.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we and others have been reported that gradual periosteum elevation creating a space over bone surface results in new bone formation in this space. 1116 These studies clearly suggest that elevating periosteum and providing space over bone surface elicit new bone formation. However, the invasion of the created space with highly competitive nonosteogenic soft tissue and poor quality of the newly formed bone are the main drawbacks of this technique.…”
Section: Introductionmentioning
confidence: 91%
“…In another experiment, the graft which was implanted in the distracted area between the alveolar bone and β -TCP block could stably exist [45]. Zakaria et al [27] then tried to use biodegradable poly-L-lactide/hydroxyapatite (PLLA/HA) mesh (Figure 1(d)) to replace the titanium mesh for distracting periosteum. Recently, Dziewiecki et al [37] compared nondegradable titanium to degradable devices (poly-DL-lactide and polyglycolic acid) in PDO; they also proved that degradable devices could produce new bone and there were no significant differences in the amount of newly formed bone between titanium and degradable materials.…”
Section: The Designs and Materials Of Distraction Devicesmentioning
confidence: 99%
“…However, Saulacic et al [36] believed that the high speed of distraction might be beneficial to periosteal osteogenesis, although it was easy to cause the disruption of wound and exposure of the device. Zakaria et al [27, 28] designed a new type of device, by means of the inclined structure; this device could be used to study the effect of different distraction rates at the same time. The result suggested that the optimal speed of distraction should be lower than 0.33 mm/d.…”
Section: Effect Of Distraction Strategies On the Formation Of New mentioning
confidence: 99%
“…Analyzing the molecular events leading to successful DO has important clinical implications, since this is a fundamental step toward the evolution of targeted therapeutic interventions designed to accelerate osseous regeneration during distraction. Current research that is focused on the development of minimally invasive approaches; stem cells; biodegradable multiplanar distraction devices (Cohen & Holmes, 2001;Yamauchi, Mitsugi & Takahashi, 2007;Zakaria, Kon & Kasugai, 2012), should aim at decreasing the distraction and consolidation times, reducing complications, and optimizing patient outcomes.…”
Section: The Futurementioning
confidence: 99%